Межі дослідження при розгляді та вирішенні скарги суддею та прокурором у досудовому провадженні - Пшенічко, Станіслав Олексійович; Пшеничко, Станислав Алексеевич; Pshenichko, S. (My University, 2012)
Article is devoted to the problem of the limits of research in reviewing and resolving complaints by the judge and prosecutor in pretrial proceedings. It is concluded that the limits of research in reviewing and resolving complaints of prosecutor is determined by its inner conviction. The judge should be limited to an initiative of the parties in determining the limits of research in resolving the complaint.
Пшенічко С. О. Межі дослідження при розгляді та вирішенні скарги суддею та прокурором у досудовому провадженні / С. О. Пшенічко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 390-396.
Keywords: межі дослідження скарги суддею та прокурором у досудовому провадженні; внутрішні переконання прокурора; обмеження судді ініціативою сторін; пределы исследования жалобы судьей и прокрором в досудебном производстве; внутренние убеждения прокурора; ограничение судьи инициативой сторон; the limits of the study and complaint judge prokrorom in pre-trial proceedings; inner convictions prosecutor; Judge sides limitation initiative